Building Confianza: Collective Public History in the Time of Distance – a Joint Reflection from the Boyle Heights Museum Team. Issue 375 (17th February 2022) - Leal, Jorge N.; Navarrete Hunter, Yesenia; Vasquez Ruiz, Michelle; Flores‐Montaño, Cassandra; Delgado, Arabella; Noriega‐Rocha, Rosa; Galeno, Isis; Rodriguez, Ivonne; Polt‐Gifford, Alexander
Abstract: How do you preserve the history of a neighbourhood undergoing change? How do you honour its residents and their legacy of lucha (struggle)? How do you uplift the voices of community members, students and researchers of colour in the museum world? In this joint reflection, members of the Los Angeles Boyle Heights Museum (BHM) reflect on their collaborative endeavours to research, preserve and celebrate the multi‐ethnic history of this Los Angeles (LA) neighbourhood. As a research, exhibition and educational project led by professors, graduate students, undergraduate students and community members, the BHM team uses a horizontal leadership model to uplift and tell the stories of a neighbourhood. The BHM team members discuss the various approaches they use to build confianza – trust – among themselves and within US Latinx migrant communities. By centring confianza as both a method and a theoretical framework for public history work, the team demonstrates how it builds a more inclusive, family‐centred and intergenerational museum experience. Through building confianza, the team has been able to pivot their work to address and manoeuvre new challenges during the Covid‐19 pandemic.